Enhanced properties of sulfonated polyether ether ketone proton exchange membrane by incorporating carboxylic-contained zeolitic imidazolate frameworks. (5th August 2020) - Hu, Fuqiang; Wen-Chin, Tsen; Zhong, Fei; Zhang, Bingqing; Wang, Jie; Liu, Hai; Zheng, Genwen; Gong, Chunli; Wen, Sheng
Abstract : Carboxylic-containing zeolitic imidazolate frameworks (ZIF-COOH) showed an obvious improvement in the performance of sulfonated polyether ether ketone (SPEEK)-based proton exchange membranes. Abstract : Carboxylic contained zeolitic imidazolate frameworks (ZIF-COOH) were designed and synthesized using 1 H -Imidazole-2-carboxylic acid and Zn(NO3 )2 ·6H2 O. The ZIF-COOH was then applied in the fabrication of composite membranes with sulfonated polyether ether ketone (SPEEK) (SPEEK/ZIF-COOH). The properties of the composite membranes, including mechanical strength, proton conductivity, and methanol permeability were studied. The incorporation of ZIF-COOH generated a significant effect on SPEEK/ZIF-COOH composite membranes, due to the special structure and compositional characteristics of ZIF-COOH. In particular, the tensile strength of SPEEK/ZIF-COOH-5 showed an enhancement of 44.1 MPa, which was 42% higher than the pristine SPEEK. Simultaneously, the proton conductivity displayed an improvement of 46% as compared to the SPEEK. Most importantly, the methanol permeability values decreased to 1.1 × 10 −7 cm 2 s −1, which was only a tenth of the value of SPEEK.